Extended genetic diagnostics for children with profound sensorineural hearing loss by implementing massive parallel sequencing. Diagnostic outcome, family experience and clinical implementation - Elander, Johanna; Ullmark, Tove; Ehrencrona, Hans; Jonson, Tord; Piccinelli, Paul; Samuelsson, Sofie; Löwgren, Karolina; Falkenius-Schmidt, Karolina; Ehinger, Johannes; Stenfeldt, Karin; Värendh, Maria (International journal of pediatric otorhinolaryngology, 2022)
The aim of this study was to investigate genetic outcomes, analyze the family experience, and describe the process of implementing genetic sequencing for children with profound sensorineural hearing loss (SNHL) at a tertial audiological center in southern Sweden. This is a prospective pilot study including eleven children with profound bilateral SNHL who underwent cochlear implant surgery. Genetic diagnostic investigation was performed with whole exome sequencing (WES) complemented with XON-array to identify copy number variants, using a manually curated gene panel incorporating 179 genes associated with non-syndromic and syndromic SNHL. Mitochondrial DNA (mtDNA) from blood was examined separately. A patient reported experience measures (PREM) questionnaire was used to evaluate parental experience. We also describe here the process of implementing WES in an audiology department. Six female and five male children (mean 3.4 years, SD 3.5 years), with profound bilateral SNHL were included. Genetic variants of interest were found in six subjects (55%), where three (27%) could be classified as pathogenic or likely pathogenic. Among the six cases, one child was found to have a homozygous pathogenic variant in MYO7A and two children had homozygous likely pathogenic variants in SLC26A4 and PCDH15, respectively. One was carrying a compound heterozygote frameshift variant of uncertain significance (VUS) on one allele and in trans, a likely pathogenic deletion on the other allele in PCDH15. Two subjects had homozygous VUS in PCDH15 and ADGRV1, respectively. In five of the cases the variants were in genes associated with Usher syndrome. For one of the likely pathogenic variants, the finding was related to Pendred syndrome. No mtDNA variants related to SNHL were found. The PREM questionnaire revealed that the families had difficulty in fully understanding the results of the genetic analysis. However, the parents of all eleven (100%) subjects still recommended that other families with children with SNHL should undergo genetic testing. Specifically addressed referrals for prompt complementary clinical examination and more individualized care were possible, based on the genetic results. Close clinical collaboration between different specialists, including physicians of audiology, audiologists, clinical geneticists, ophthalmologists, pediatricians, otoneurologists, physiotherapists and hearing habilitation teams was initiated during the implementation of the new regime. For all professionals involved, a better knowledge of the diversity of the genetic background of hearing loss was achieved. Whole exome sequencing and XON-array using a panel of genes associated with SNHL had a high diagnostic yield, added value to the families, and provided guidance for further examinations and habilitation for the child. Great care should be taken to thoroughly inform parents about the genetic test result. Collaborations between departments were intensified and knowledge of hearing genomics was increased among the staff.